Synthesis of novel tantalum oxide sub-micrometer hollow spheres with tailored shell thickness - Agrawal, Mukesh (Langmuir : the ACS journal of surfaces and colloids, 2008)
Sub-micrometer-sized hollow tantalum oxide (Ta2O5) spheres with tunable shell thickness and void size have been fabricated exploiting beta-diketone-functionalized polystyrene (PS) beads as sacrificial templates in a sol-gel process. First, a controlled precipitation of Ta2O5 nanoparticles was carried out on the template surface by hydrolyzing tantalum ethoxide (Ta(OEt)5) at room temperature, and subsequently, the polymer core was removed either via chemical treatment with toluene or calcination at 650 degrees C. The thickness of the tantala shell precipitated on the PS core during the coating process was tuned between 100 and 142 nm by varying the concentration of tantala precursor in the reaction media. The obtained Ta2O5-coated PS particles and hollow microspheres were characterized by scanning electron microscopy, transmission electron microscopy, infrared spectroscopy, X-ray diffraction, and thermogravimetric analysis. Due to the unique optical and dielectric properties, these nanostructured materials are envisaged to be used in applications such as novel building blocks for the fabrication of advanced materials, surface coatings, catalysts, and drug delivery systems